2012
DOI: 10.1542/peds.2011-2157
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement Varies With Gestational Age Among Children Born at Term

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Late preterm infants are at risk for a variety of developmental impairments; however, little is known about developmental differences among children born within the term range of 37 to 41 weeks' gestation. WHAT THIS STUDY ADDS:This study links comprehensive birth record data from 128 050 term births to children' s school records 8 years later. Analyses establish that, even among the "normal term" range, gestational age is an important independent predictor of academic achievement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
130
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 31 publications
15
130
0
3
Order By: Relevance
“…Although there was no significant correlation between gestational age and intelligence quotient for the 8-year-old children (r ϭ Ϫ0.09, P ϭ .49) in our study, population-based studies have shown that white matter development is associated with cognitive functioning in 6 -10-year-old healthy children, 18 and recent large-scale studies have revealed associations between cognitive development and length of gestation in school-age children born at term. [12][13][14][15] Our results indicate that white matter changes are not likely the driving force for reported relationships between gestational age and cognitive performance in term-born children. It is noteworthy that reported white matter changes in older children/ adolescents associated with preterm birth were mostly for those born very preterm or with very low birth weight, [3][4][5]8,26 and a study of 9-year-old children with low risk preterm birth (30 -34 weeks of gestation) showed more changes in gray matter than white matter compared with term controls.…”
Section: Figmentioning
confidence: 61%
See 1 more Smart Citation
“…Although there was no significant correlation between gestational age and intelligence quotient for the 8-year-old children (r ϭ Ϫ0.09, P ϭ .49) in our study, population-based studies have shown that white matter development is associated with cognitive functioning in 6 -10-year-old healthy children, 18 and recent large-scale studies have revealed associations between cognitive development and length of gestation in school-age children born at term. [12][13][14][15] Our results indicate that white matter changes are not likely the driving force for reported relationships between gestational age and cognitive performance in term-born children. It is noteworthy that reported white matter changes in older children/ adolescents associated with preterm birth were mostly for those born very preterm or with very low birth weight, [3][4][5]8,26 and a study of 9-year-old children with low risk preterm birth (30 -34 weeks of gestation) showed more changes in gray matter than white matter compared with term controls.…”
Section: Figmentioning
confidence: 61%
“…[6][7][8] The effects of gestational age on neurologic or neurodevelopment for term-born children (Ն37 completed weeks of gestation) have not been investigated until recently. Several new studies (most of them population-based) reported positive associations between longer gestational age (excluding postterm, which is Ն42 weeks of gestation) and better cognitive and/or neurodevelopment in term-born children, such as higher scores on Bayley scales of mental and motor development during the first year of life 9,10 ; more school readiness and cognitive and educational ability at age 3 years 11 ; higher intelligence quotient scores 12 and less vulnerability to low early developmental index at age 6 -7 years 13 ; greater reading, math, and achievement scores in the third grade 14 ; and better test scores in elementary and middle school and higher probability of being gifted. 15 Brain structural and functional development is directly related with neurodevelopment and cognitive performance in children.…”
mentioning
confidence: 99%
“…Some observational studies have suggested a possible association between delivery at "earlyterm" gestations (37 to 39 weeks) versus "lateterm" gestations (40 to 41 weeks) [11][12][13][14] and a subtle long-term effect on children's development and educational attainment. However, data from randomized trials to inform outcomes in infants after discharge from the hospital are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its benefits may be offset by longer-term adverse outcomes in children because of delivery at "early-term" gestation (37 to 39 weeks). [11][12][13][14] Some obstetricians in the United Kingdom already induce labor at the due date (40 weeks of gestation); rates of induction are 39% among women 40 to 44 years of age and 58% among women 45 years of age or older. Among obstetricians who do not induce labor in older pregnant women at the due date, one third are reluctant to offer induction because they are concerned about increasing the likelihood of cesarean delivery, even though they think that induction would improve perinatal outcomes.…”
mentioning
confidence: 99%
“…The definition of "term", has recently been refined to classify neonates as early (37-39 wk gestation), full (39-41 wk gestation), late (41-42 wk gestation), or post-term (≥ 42 wk gestation) (6). Early-term neonates are at higher risk of nonoptimal developmental outcomes compared to infants born at 39 wk gestational age (GA) or later (7). At this time, little is known about iron status in healthy, term neonates born to pregnant adolescents and on relative changes in iron stores that can be accrued over the last 3-5 wk of gestation.…”
mentioning
confidence: 99%